FORMULASI RANSUM BERBAHAN IKAN PATIN DAN TEMPE SEBAGAI ALTERNATIF PANGAN DARURAT LANSIA - Sahrin Meizia Huzaifa; Widi Hastuti; Fred Agung Suprihartono; Mamat Rahmat; Putu Bunga Fitridewi (Jurusan Gizi Poltekkes Kemenkes Bandung, 2026)
The impact of natural disasters on food security in Indonesia raises special nutritional problems in the nutritional status of the elderly who are vulnerable to malnutrition. Prevention of malnutrition in disaster conditions can be done by consuming high-protein foods such as catfish and tempeh. The ration product consists of instant rice, tempeh catfish balls, and dried vegetables that can be used as an alternative disaster ration for the elderly. This study aims to determine the quality analysis and formulation of rations made from catfish and tempeh as an alternative emergency food product for the elderly. The research design was an experimental study with a one-factor Completely Randomized Design (CRD) with 3 treatments: F1 (50%:50%), F2 (60%:40%), and F3 (70%:30%). The research method used hedonic test of organoleptic properties, kjeldahl for protein content, gravimetry for fat content, and by difference for carbohydrate content. Kruskal wallis test result showed there was an effect of catfish and tempeh formulation on taste (p=0.016), but No. effect on color (p=0.195), aroma (p=0.190), texture (p=0.708), and overall (p=0.506). The results of organoleptic testing, the most superior formula, namely F2 with an average value of 5.96. Tempeh catfish balls per serving (96 g) contain 195.2 kcal of energy, 11.86 g of protein, 9.9 g of fat, and 14.7 g of carbohydrates and have met emergency food requirements. It is hoped that further research can be carried out on shelf-life testing of ration products, either using the direct method (real time) or the estimation method (Accelerated Shelf-Life Testing/ASLT).